The Super Mario Bros. super show! Mario of the deep - Nintendo of America Inc.; NCircle Entertainment; DIC Entertainment (Firm) (Dallas, TX : NCircle Entertainment, 2007)
The incredible adventures of the Mario Brothers in their battle against the ever-threatening King Koopa.
Rollin' down the river -- Pirates of the Koopa -- Mario of the deep -- 20,000 Koopas under the sea -- The Koopas are coming!
Based on the Nintendo video game.
Originally broadcast on television in 1989.
DVD.
videodisc.
Keywords: Super Mario Bros. (Game) -- Juvenile films; Plumbers -- Juvenile films; Brothers -- Juvenile films; Animated television programs; Fantasy television programs